The Mode of Trench-Parallel Subduction of the Middle Ocean Ridge - Shen, Xiaobing; Leng, Wei (Frontiers in Earth Science, 2021)
Trench-parallel subduction of mid-ocean ridges occurs frequently in plate motion history, such as along the western boundary of the Pacific plate in the early Cenozoic and along the eastern boundary of the Pacific plate at present. Such subduction may strongly alter the surface topography, volcanic activity and slab morphology in the mantle, whereas few studies have been conducted to investigate its evolutionary process. Here, we construct a 2-D viscoelastoplastic numerical model to study the modes and key parameters controlling trench-parallel subduction of mid-ocean ridges. Our model results show that the subduction modes of mid-ocean ridges can be primarily categorized into three types: the fast spreading mode, the slow spreading mode, and the extinction mode. The key factor controlling these subduction modes is the relative motion between the foregoing and the following oceanic plates, which are separated by the mid-ocean ridge. Different subduction modes exert different surface geological expressions, which may explain specific evolutionary processes related to mid-ocean ridge subduction, such as topographic deformation and the eruption gap of volcanic rocks in East Asia within 55–45 Ma and in the western North American plate during the late Cenozoic.